Pedagogical Practices in Teaching Cohesive Devices in EFL Writing Courses: A Case Study at Fezzan University - Ali Abdullah Ahmad Albayyan; Siti Nur'aini; Arso Setyaji; Amnnah Abdulwahhab (English Tadris Department, Tarbiyah and Teacher Training Faculty, Datokarama State Islamic University Palu, 2026)
Academic writing remains a challenge for university-level EFL learners, particularly in producing coherent texts through the effective use of cohesive devices. In the Libyan EFL context, previous studies have mainly examined cohesion errors in students’ writing, while limited attention has been given to the pedagogical and curricular practices that shape students’ use of cohesive devices. This study investigates how cohesive devices are taught within the writing curriculum of the English Department at Fezzan University. Using a descriptive qualitative case study design, the study involved syllabus analysis of five writing courses, questionnaires administered to 20 undergraduate students, and semi-structured interviews with five writing lecturers. The analysis was guided by Renandya et al.’s (2021) “Bridging the Reading–Writing Gap” framework to examine reading-writing integration across curriculum, teaching practices, and student learning experiences. The findings revealed that although the writing courses follow a logical progression from sentence-level writing to advanced academic writing, cohesive devices are mostly addressed implicitly rather than through systematic discourse-level instruction. Lecturers primarily emphasized grammar and vocabulary, while cohesion was treated as a secondary skill acquired through writing practice. The study suggests that integrating reading and writing instruction with explicit teaching of cohesive devices may better support students’ academic writing development.